Pengaruh Pemberdayaan Karyawan, Kerja Tim, dan Pelatihan terhadap Kepuasan Kerja - Novia Resnadita (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
This study aims to determine and explain the effects of employee empowerment, teamwork and training on job satisfaction at Human Resource Management and Marketing & Customer Services of PDAM Surya Sembada Kota Surabaya with a sample size of 60 respondents to employees at Human Resource Management and Marketing & Customer Services of PDAM Surya Sembada Kota Surabaya. The statistical analysis used in this study was SPSS. The results of this study indicate that employee empowerment does not affect job satisfaction, teamwork does not affect job satisfaction and training has a significant positive effect on job satisfaction.